Association of Selected Non Communicable Diseases with Sleep Behaviour among the Rural Geriatric Population in the Northern Districts of Tamil Nadu, India: A Cross-sectional Study - R Suba Shree; R Kalaivanan; Roshni Mary Peter; M Logaraj (Journal of Clinical and Diagnostic Research)
Introduction: Non Communicable Diseases (NCDs) and sleep disturbances are significant health concerns, especially among the elderly. Understanding the association between behavioural factors, NCDs and sleep quality in rural geriatric populations is crucial for developing effective interventions. Aim: To estimate the prevalence of selected NCDs and to assess the relationship between these NCDs and sleep behaviour among the rural geriatric population in the northern districts of Tamil Nadu, India. Materials and Methods: A cross-sectional study was conducted from July 2018 to May 2020 among 7,200 elderly individuals (≥ 60 years), selected using multistage stratified random sampling from the Chengalpattu, Kancheepuram and Thiruvannamalai districts. Data on socio-demographic variables, behavioural factors (e.g., smoking, tobacco chewing, alcohol use), sleep patterns and NCDs (e.g., hypertension, diabetes, depression) were collected using validated tools. Statistical analyses, including Chi-square tests and logistic regression, were performed to identify associations. Results: The prevalence of poor sleep was found to be 4,580 (64%), with a higher proportion among females {Odds Ratio (OR)=1.25, p-value <0.001} and unmarried individuals (OR=1.36, p-value <0.001). A total of 2,728 (37.9%) study participants had hypertension, 1,284 (17.8%) had diabetes and 4,043 (56.2%) had depression. Depression was significantly associated with poor sleep (OR=1.52, p-value <0.001), while 1,758 (38.4%) participants with poor sleep reported hypertension and 17.8% reported diabetes. No significant associations were found between these NCDs and sleep quality. Conclusion: The present study emphasises that the rural elderly population has an elevated risk of inadequate sleep. Poor sleep was significantly predicted by depression, highlighting the necessity for integrated mental health interventions for the elderly. Targeted behavioural and psychological therapies to address sleep issues may enhance the overall well-being and quality of life of this vulnerable population.